Analisa Pengaruh Katalis Terhadap Gas Buang Pada Kendaraan Roda 2 - Akbar Ramadhan Firman Al Abrari; Listiyono Listiyono (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The impact of the increase in motorized vehicles is air pollution from vehicle exhausts. Exhaust gas is a polluting substance that pollutes the air where the gas is created from exhaust gas or gas from the combustion of vehicles. One alternative way to reduce the content of harmful exhaust gases such as carbon monoxide (CO), and hydrocarbons (HC) produced by motorized vehicles is by adding a catalytic converter. In this study, the catalytic converter uses Aluminum (Al), Brass (Cu-Zn), and Copper (Cu) materials. The purpose of this study is to analyze the effect of using a catalytic converter made of Aluminum (Al), Brass (Cu-Zn), and Copper (Cu) on exhaust gas. In addition, this study aims to determine the material used as a catalytic converter in order to get the lowest level of exhaust gas. Furthermore, the research data are presented in tabular form and then analyze them using one way anova and graphs. The results showed a decrease in CO by 50% at 1500 Rpm and 59.6% at 4500 Rpm, HC by 72% at 1500 Rpm and 55% at 4500 Rpm, CO2 by 3.22% at 1500 Rpm and 7.91% at 4500 Rpm, and O2 by 5.53% at 1500 Rpm and 1.66% at 3000 Rpm.